The Role and Strategy of the Association of Southeast Asian Nations (ASEAN) in Protecting Migrant Fishers in Southeast Asia Against Modern Slavery - Belardo Prasetya Mega Jaya; Muhammad Rusli Arafat; Asep Hakim Zakiran; Mohd Hazmi Mohd Rusli; Noor Dzuhaidah Osman; Amalina Ahmad Tajudin (USIM Press, 2025)
Indexed by WOS/Scopus/ERA